1999
DOI: 10.1080/14017439950141407
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-a Serum Activity During Treatment of Acute Decompensation of Cachectic and Non-Cachectic Patients with Advanced Congestive Heart Failure

Abstract: Tumor necrosis factor-alpha (TNF-alpha) is a proinflammatory cytokine that produces left ventricular dysfunction and a negative inotropic effect in cardiac tissue when overexpressed in human subjects. Previous studies have shown that levels of circulating TNF-alpha are elevated in patients with advanced congestive heart failure (CHF) and especially in those with cardiac cachexia. To clarify the potential role of TNF-alpha in the unstable state of decompensated advanced CHF, we investigated the TNF-alpha serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Clinical studies have shown elevated serum levels of TNF-α in patients with decompensated CHF, especially in those with cachexia [107]. There is further good evidence from experimental studies that TNF-α has an immediate negative effect on contractile function [35, 155] and the economy of contraction [67].…”
Section: Therapeutic Approaches In Clinical Trialsmentioning
confidence: 99%
“…Clinical studies have shown elevated serum levels of TNF-α in patients with decompensated CHF, especially in those with cachexia [107]. There is further good evidence from experimental studies that TNF-α has an immediate negative effect on contractile function [35, 155] and the economy of contraction [67].…”
Section: Therapeutic Approaches In Clinical Trialsmentioning
confidence: 99%